Enhanced Electrochemical Performance of 5V LiNi0.5Mn1.5‐xZrxO4 Cathode Material for Lithium‐Ion Batteries. Issue 28 (26th July 2021) - Gong, Jiajia; Fu, Shaoxiong; Zhang, Yuan; Yan, Shuaipeng; Lang, Yaqiang; Guo, Jianling; Wang, Li; Liang, Guangchuan
Abstract: Series of LiNi0.5 Mn1.5‐x Zrx O4 (x=0, 0.0025, 0.005, 0.01, 0.02) samples have been prepared by a combined coprecipitation‐hydrothermal method followed by two‐step calcination. The effects of Zr 4+ doping contents on the structure, morphology and electrochemical properties are studied. The results show that Zr 4+ doping reduces Mn 3+ content and Ni/Mn disordering degree. Additionally, Zr 4+ doping reduces primary particle size and agglomeration degree. More significantly, Zr 4+ doping leads to the appearance of higher‐surface‐energy 110 and/or 311 facets, while undoped sample only consists of 111 and 100 facets. But excessive Zr 4+ doping (x=0.02) leads to the decrease of higher‐surface‐energy facets. Electrochemical results show that appropriate Zr 4+ doping improves the rate and cycling performances of LiNi0.5 Mn1.5 O4 material. Among them, LiNi0.5 Mn1.495 Zr0.005 O4 shows the optimal electrochemical performance, which can be attributed to high phase purity, high crystallinity, appropriate primary particle size and agglomeration degree, enlarged lattice constant, and greater exposure of 110 and/or 311 facets. Abstract : LiNi0.5 Mn1.5‐x Zrx O4 samples were prepared by coprecipitation‐hydrothermal method followed by two‐step calcination. The effects of Zr 4+ doping contents on the structure, morphology and electrochemical properties were studied. Zr 4+ doping reduces primary particle size and agglomeration degree. Appropriate Zr 4+ doping induces the appearance of higher‐surface‐energy 110 and/or 311 facets, leading to the improved rate and cycling performances of LiNi0.5 Mn1.5 O4 material.